(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2015)
The microbiological fertilizer Baikal EM-1 contains lactic acid bacteria, photosynthetic bacteria, nitrogen fixing bacteria, Saccharomyces yeasts and microbial cultivation media. The aim of the present study was to evaluate the impact of it on onion grown in controlled greenhouse conditions. In summer 2014 two trials with this product were carried out on onions in greenhouse conditions. Before planting onion bulbs were soaked in water with added fertilizer and growth substrate was watered with the fertilizer according to the instructions of manufacturer. During the vegetation period plants were watered with the fertilizer several times. Identical treatment was performed with water in the control plots. Different treatment schemes and growth substrates (neutralized peat and substrate for vegetables) were used in both trials. The main difference of the used substrates was in the content of mineral nutrients that was higher in the substrate for vegetables. In the second trial additional fertilization with ammonium nitrate was applied three times during the vegetation period. At the end of the trials the yield of onion leaves was estimated, as well as the length of leaves and their chlorophyll content was measured. At the first trial the obtained yield of onion leaves was increased by 6.4 % and in the second by 8.2 % due to treatment with Baikal EM-1 but these differences were not statistically significant in comparison to the control plots. In general, the fertilizer increased all other measured parameters as well, including average length of leaves by 4.6 % and 1.3 %, the chlorophyll content by 5.0 % and 1.5 %, in the first and second trial respectively, and percentage of onions developing leaves increased by 13.2 % in the second trial. Only the last parameter showed statistically significant differences in comparison to the control. Additionally the growth of the onion was more even in the control treatment. In conclusion, the microbiological fertilizer Baikal EM-1 gave positive impact on onions in greenhouse conditions.